2017
DOI: 10.1016/j.apacoust.2016.06.010
|View full text |Cite
|
Sign up to set email alerts
|

The implementation of low-cost urban acoustic monitoring devices

Abstract: The urban sound environment of New York City (NYC) can be, amongst other things: loud, intrusive, exciting and dynamic. As indicated by the large majority of noise complaints registered with the NYC 311 information/complaints line, the urban sound environment has a profound effect on the quality of life of the city's inhabitants. To monitor and ultimately understand these sonic environments, a process of long-term acoustic measurement and analysis is required. The traditional method of environmental acoustic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
114
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 111 publications
(115 citation statements)
references
References 16 publications
1
114
0
Order By: Relevance
“…Taking into account these technical microphone's features and a large number of inverse filter coefficients, we concluded that a costly inverse filter of the microphone's frequency response cannot be implemented on a system with limited resources, and it is not necessary for the Category 3 device, as classified in [21]. The calibration of the final sound level meter is sufficient and this has been also confirmed by the results in Section 5.…”
Section: The Microphonesupporting
confidence: 58%
See 3 more Smart Citations
“…Taking into account these technical microphone's features and a large number of inverse filter coefficients, we concluded that a costly inverse filter of the microphone's frequency response cannot be implemented on a system with limited resources, and it is not necessary for the Category 3 device, as classified in [21]. The calibration of the final sound level meter is sufficient and this has been also confirmed by the results in Section 5.…”
Section: The Microphonesupporting
confidence: 58%
“…The results of 12-minute measurements in the indoor environment showed that the proposed sensor node closely follows values registered by Class 1 Sound Level Meter with the mean difference less than 2 dB. Thus, according to [21], the proposed solution belongs to the Category 3 -Low-cost sensor network, which consists of custom-made nodes designed to be inexpensive, low-power and autonomous for large-scale deployments. The proposed sensor node is a promising and viable solution for measurement in application scenarios where legally enforceable sound level data are not needed but measurements are sufficient for informative screening of noise levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the potential applications of the Audio-Annotator tool is to annotate sounds captured by an urban acoustic sensor network [34]. Therefore, we based the audio stimuli on soundscapes of urban sound events related to traffic, construction and other types of human activity.…”
Section: Audio Stimulimentioning
confidence: 99%